Communicable Diseases Intelligence volume 3 issue 16 - 17 August 1979 - whole issue - No author listed, (Communicable Diseases Intelligence, 1979)
Whole-issue pdf, comprising: Virus reports this period Articles Cholera - Melbourne, Victoria. Isolation of strains of Neisseria meningitidis W 135 in South Australia Special vaccines held by the Commonwealth Serum Laboratories (C.S.L.) [List of currently available vaccines] International notes. Scarring following BCG and smallpox vaccination - Algeria Evaluation of transport media for the recovery of Campylobacter fetus subsp. je juni Poliomyelitis in contact of vaccine recipient in the U.K. Administrative notes: - Virus tables - Salmonella reporting Australia - Communicable Diseases Intelligence Reporting Period - 26/07/1979 to 08/08/1979 Bulletin Number 79/16